Assessing individualized instruction in the classroom: Comparing teacher, student, and observer perspectives. (December 2022) - Tetzlaff, Leonard; Hartmann, Ulrike; Dumont, Hanna; Brod, Garvin
Abstract: In this article, we address the measurement of individualized instruction in the context of regular classroom instruction. Our study assessed instructional practices geared towards individualization in German third grade reading lessons by combining self-report data from 621 students, from their teachers (n = 57), and live observations. We then investigated the reliability of these different approaches to measuring individualization as well as the agreement between them. All three approaches yielded reliable indicators of individualized practices, but not all of them corresponded with each other. We found considerable agreement between students and observers, but neither agreed with teachers' self-reports. Upon closer examination, we found that students' ratings only correlated with teacher ratings that were provided close to the timepoint of interest. This correlation increased when teacher measures were corrected for response tendencies. We conclude with some recommendations for future studies that aim to measure individualized instruction in the classroom. Highlights: Individualized instruction can be reliably assessed from different perspectives. The ratings of students and external observers are significantly correlated. Retrospective teacher ratings correlate with student ratings, trait measures do not. Correcting teacher ratings for biases increases correspondence to other perspectives.